Analysis of medical and dentistry basic sciences examinations: A case study - Nasrin Khajeali; Maryam Aslami; Marzieh Araban (Payesh, 2020)
Objective (s): Multiple choice questions are the central core of the evaluation of medical students. The purpose of this study was to analyze medical and dentistry basic sciences examinations in Ahvaz Jundishapur University of Medical Sciences in 2015. Methods: A valid checklist for totally 450 multiple choice questions (225 questions for each field), were analyzed in terms of structure, difficulty index, discrimination index and diversion options. Structure of the questions was analyzed by a checklist consisting of 16 items with yes or no formats. Difficulty and discrimination indexes for each question also were examined. To analyze the data, descriptive statistics were used. Results: There were structural problems with 6 and 5 percent of medical and dentistry questions respectively. In For medical examination on average 50.1% required difficulty indexes, 25.8% required discrimination indexes and 73.5% diversion options were achieved. For dentistry examination on average 50.07% required difficulty indexes, 23.07% required discrimination indexes and 53.46% diversion options were achieved. Conclusion: The findings indicated that frequency of the questions with required difficulty index, were rather good but frequency of the questions with required discrimination index, were relatively very low. Diversion options in medical questions were designed better than dentistry questions. Indeed, it seems that examinations of medical and density students need some revisions and corrections.